Use of Eltrombopag in Children With Chronic Immune Thrombocytopenia (ITP): A Real Life Retrospective Multicenter Experience of the Italian Association of Pediatric Hematology and Oncology (AIEOP) - Giordano, Paola; Lassandro, Giuseppe; Barone, Angelica; Cesaro, Simone; Fotzi, Ilaria; Giona, Fiorina; Ladogana, Saverio; Miano, Maurizio; Marzollo, Antonio; Nardi, Margherita; Notarangelo, Lucia Dora; Pession, Andrea; et al. (Frontiers in Medicine, 2020)
Background: the thrombopoietin receptor agonist eltrombopag has been shown to be safe and effective for children with chronic immune thrombocytopenia (ITP). The aim of the present study was to characterize eltrombopag use in current clinical practice. Material and methods: This is a retrospective multicentre study conducted in 17 centres affiliated to the Italian Association of Pediatric Haematology and Oncology (AIEOP). The primary objective of the study was to determine the prevalence of eltrombopag use in Italian children affected by chronic ITP, after EMA authorization for pediatric age. The secondary objective was to assess efficacy in the first 6 months and safety during the whole period of eltrombopag treatment in current clinical practice. A total of 386 children with chronic ITP were retrospectively enrolled and eligible for analysis. Among these patients, 71 received eltrombopag. Results: the prevalence of eltrombopag use was 19% (95% CI 0.15 – 0.23). Thirty-one patients (44%) were male and forty patients (56%) were female. The median age at the first dose of eltrombopag was 12 years (3-17 years). The median duration of eltrombopag treatment was 11 months (1-32 months) and the median starting dose was 50 mg/day (12,5-75 mg/day). Thirty-two patients (45%) required one or more concomitant ITP medications during the first six months of treatment with eltrombopag. Thirty-nine patients (55%) never required concomitant medications. Median platelet counts and proportion of patients achieving the target platelet count of at least 30 × 109/l and 100 × 109/l significantly increased during the first six months of treatment (p value < .0001). Additionally, eltrombopag has been proved effective in the absence of concomitant therapies. The most common Adverse Events were headache (7%) and thrombocytosis (6%). Conclusion: Our study highlighted the crucial role of eltrombopag as second line treatment in children with chronic ITP.